PSYCHOLOGICAL AND PEDAGOGICAL BASICS OF FORMING THE COMMUNICATIVE CULTURE OF FUTURE EDUCATORS OF IPE: AN INTERDISCIPLINARY APPROACH - Marchii-Dmytrash, Tamara; Kyrsta, Nataliia; Matishak, Marianna (Mountain School of Ukrainian Carpaty, 2022)
The article focuses on the fact that in the process of professional training, it is necessary to ensure the proper level of forming of the communicative culture of future educators of institutions of preschool education (IPE), and also substantiates its psychological and pedagogical foundations in the context of an interdisciplinary approach. Various approaches to the interpretation of the concepts "culture of communication", "communication ethics", "communicative culture", "communicative competence" have been analyzed. In order to form the communicative culture of future teachers of IPE, it is important to implement a humanistic paradigm of education, which involves partnership interaction of participants in the educational process, student-centeredness in the broad sense, a variety of activities of education seekers, a personally oriented style of communication, interaction and benevolent demandingness. An interdisciplinary approach in the context of the researched problem ensures systematicity, integrity and integration of scientific knowledge for the effective forming of the communicative culture of future educators. The psychological foundations of the specified process during the study of the disciplines of the psychological-pedagogical cycle and the teaching methods of individual disciplines, taking into account the interdisciplinary approach, are determined, in particular, the enrichment of the content of educational components with relevant scientific knowledge about the essence of the concepts of "communication", "communicative culture", the study of age and individual-psychological features of communication with preschool age children, their parents and other persons of the educational process in the IPE, assimilation of rules and ethical norms of communication; the usage of interactive forms and methods of learning during mastering the program content of the disciplines; interaction of participants in the educational process on the basis of partner pedagogics. The main idea of the article is that the culture of speech is actively formed in preschool age children (phonetically and orthographically correct and clean pronunciation of sounds, words and phrases, mastering the cultural norm of language, etc.), accordingly, it is important that the teacher of IPE was a role model and perfectly possessed communicative culture. Keywords: communicative culture, communication, future educator, institution of preschool education (IPE), professional training, interdisciplinary approach, institution of higher education, educational component, educational process.